Extra care: viable for couples living with dementia?. Issue 1 (20th March 2017) - Poyner, Christopher; Innes, Anthea; Dekker, Francesca
Abstract : Purpose: The perspectives of people with dementia and their care partners regarding "extra care" housing are currently unknown. The purpose of this paper is to report findings of a consultation study exploring the perceived barriers and facilitators of a relocation to extra care housing, from the perspective of people living with dementia, and their care partners. Design/methodology/approach: Fieldwork consisted of paired or 1-1 interviews and small focus groups with potential users of an alternative model of extra care support for people living with dementia in the South of England. The consultation took place between June and August 2013. The interviews and focus groups were audio recorded, transcribed verbatim. The transcripts were analysed thematically. Findings: Benefits of extra care were identified as the opportunity for couples to remain living together for longer, creating a supportive, dementia-friendly community, and a reduction in the strain experienced by the care partners. Barriers centred on a sense of loss, stress and uncertainty. Living and caring at home was perceived as preferable to shared care. Research limitations/implications: The findings presented here have limited generalisability for two reasons. First, the shared care approach consulted on was very specific. Second, the participants form a purposive sample and as such are not representative of a wider population. Despite best intentions, the voice of people with dementia, are underreported in this consultation. Only one person with early on-set dementia was interviewed and the remaining two people with dementia were interviewed alongside their care partner. Practical implications: The findings cast doubt on the viability of extra care facilities, designed for couples living with dementia, if extra care continues to be conceptualised and marketed as a preventative lifestyle choice. The findings indicate the value of consulting with people with dementia, and their care partners, when designing new forms of housing with care specifically for people living with dementia. Social implications: The findings of this consultation exemplify the wish of couples living with dementia to remain together, in what they perceive to be "home", for as long as possible. Couples living with dementia are therefore unlikely to wish to move into an extra care facility as a lifestyle choice option, early into their journey with dementia. This raises questions about the suitability of extra care, as a form of housing with care, for couples living with dementia. Originality/value: This paper contributes to the body of literature, exploring the feasibility of new and innovative alternative care and housing options, for people with dementia. This paper is one of the first to explore extra care as a housing and social care option for couples with dementia.